Macrolide-resistant mycoplasmal infection in children: the concept of formation, modern principles of diagnosis and treatment - M.A. Gonchar; G.S. Senatorova; O.L. Logvinova; G.R. Muratov; E.M. Pushkar; E.N. Kryzhanovskaya; T.B. Ishchenko; O.P. Pomasunovska; O.V. Bondar; T.N. Ishchenko; V.V. Kornienko (Zaslavsky O.Yu., 2018)
Mycoplasma pneumoniae takes the leading place in the etiology of community-acquired pneumonia in children. The article presents the course of macrolide-resistant mycoplasmal pneumonia and modern treatment strategy based on the clinical observation of a school-age child. The authors describe the features of disease epidemiology, with the focus on the mechanisms of Mycoplasma pneumoniae resistance to macrolides. The article details the mechanisms of excessive immune response, as well as current world standards for the diagnosis and treatment of pneumonia.